The Sustainable Agricultural Innovation: The Impact of Biochar and Bioactivator Technology on the Growth Media of Banana Kepok Tanjung Seedlings - Putri, Santi Diana; Sari, Wilna; Jarlis, Roni; Fevria, Resti; Hermansah, Hermansah; Agustian, Agustian; Nurmiati, Nurmiati; Amelia, Kiki; Taufiqqurrahman, Taufiqqurrahman (Pelita Eksakta, 2025)
Innovation in sustainable agriculture is key to improving the productivity and quality of agricultural products, especially in areas with low soil fertility challenges. This service activity explored the impact of the application of Biochar and Bioactivator (BnB) technology on the growth medium of banana Kepok Tanjung seedlings in Sijunjung Regency. Biochar, which is produced from the pyrolysis of rice husks, serves to improve water retention and nutrient availability, while bioactivators accelerate the decomposition of organic matter and increase soil microbial activity. Through the method of socialization and structured demonstrations, the initial hypothesis of the activity provides an overview that the use of BnB technology significantly improves the growth parameters of seedlings, including an increase in stem diameter by 15.6% and an increase in the number of leaves by 26.2%. Statistical analysis showed a consistent Z-score and a very significant p-value (<0.001), from this hypothesis it confirms the effectiveness of this technology in improving the quality of the growth media of banana Tanjung Kepok seedlings. These findings not only provide an overview of the potential of BnB technology in banana cultivation but also offer sustainable solutions to increase agricultural productivity in areas facing similar challenges. Recommendations for follow-up service activities include optimizing application doses and evaluating long-term impacts on the sustainability of soil ecosystems.